Suprasellar mixed germ cell tumor. A case report. - Bourilhon, Facundo; Battafarano, Agustín; Calatroni, Maximiliano; Pedrazas, Ezequiel; Quintana Corvalán, Maximiliano; Romano, Anibal (Revista Argentina de Neurocirugía, 2022)
Intracranial germ cell tumors belong to a heterogeneous group which origin is unknown with certainty. The incidence is variable according to the geographical regions studied: in the West it is described from 0.4% to 3, 4% in patients with primary central nervous system tumors, in the East their number is five to eight times higher. This work has two objectives: the first is to report an infrequent case of a 23-year-old patient who was admitted due to decreased visual acuity. his MRI found a sellar-suprasellar lesion. Removal through a pterional approach was performed. The patient died approximately 5 months after the surgical procedure due to tumor progression. Our second objective is to contribute with additional bibliography to the scarce existing information on this low incidence and prevalence pathology.